A clear sky physical based solar radiation decomposition model. (June 2018) - Scarpa, Federico; Bianco, Vincenzo; Tagliafico, Luca A.
Graphical abstract: Highlights: The study focuses on the evaluation of direct and diffuse component of solar radiation. The presented approach is based on geometrical and physical considerations. The approach is limited to clear-sky, cloudless condition. Ground albedo is accounted for. A physical framework is given upon which to develop meaningful correlations. Abstract: To evaluate the performance of solar thermal or photovoltaic systems, to perform a proper assessment of thermal environment inside buildings, but also in case of climatic long-term and weather short-term forecasting, solar radiation has to be decomposed in its diffuse and beam fractions to predict the correct amount of solar energy involved in a particular context. However, solar radiation is typically disposable from weather stations as global irradiance on a horizontal plane, so that methods have to be devised to derive the required components. The task is not trivial since many factors, apart from geometrical/astronomical ones, affect the relative amount of direct and diffuse radiation; from the actual limpidity of the atmosphere to the presence and amount of clouds, to the albedo of the ground. Differently from the available literature on the subject, the present study is aimed to explicitly relate these causes and to present, under clear sky conditions, physical based correlations which are able to account for the main factors governing solar irradiation characteristics. Instead to focus only on the attenuation due to atmosphere and to deep the numerous factor it depends on or, conversely, to specify empirical correlations valid only for a given location, this paper attempts to mix these perspectives to construct more meaningful clear sky correlation based on physical laws and constraints. The main result of study is a meaningful relation representing a conceptual framework on which it possible to develop and test physical based correlations to split the solar radiation in its diffuse and direct components.